FORMULATION AND EVALUATION OF STATISTICALLY DESIGNED IBUPROFEN FASTDISSOLVING TABLETS EMPLOYING STARCH GLUTAMATE AS A NOVEL SUPERDISINTEGRANT - SANTOSH KUMAR R,; SAHITHI MUDILI, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main aim of the present work is to enhance the solubility and bioavailability of the ibuprofen by formulating it into fast-dissolving tablets employing starch glutamate as a novel superdisintegrant. Materials and Methods: Starch glutamate was prepared from native potato starch and glutamic acid by the esterification process. Drug-excipient compatibility studies were performed between the starch glutamate and ibuprofen with the help of Fourier transform infrared spectroscopy, and differential scanning calorimetry techniques. Ibuprofen fast dissolving tablets were formulated employing different superdisintegrants along with the starch glutamate (a novel superdisintegrant) by the direct compression method. The prepared ibuprofen fast-dissolving tablets were evaluated for various pre- and post-compression parameters along with the in vitro and in vivo release characteristics. Optimized formulation stability studies were performed at accelerated conditions for 6 months as per the International Conference on Harmonization (ICH) and WHO guidelines. Results: Drug-excipient compatibility studies indicated that prepared starch glutamate was compatible with ibuprofen drug, and it can be used as a superdisintegrant in the formulation of fast-dissolving tablets. Fast-dissolving tablets of ibuprofen were formulated by employing starch glutamate as a superdisintegrant showed good tablet properties and showed an increased dissolution efficiency of the drug. Among all the formulations (F1–F8), the formulation F4 which contains 5% starch glutamate and 5% croscarmellose sodium as superdisintegrants showed 99.7±0.34% drug dissolution within 5 min. Peak plasma concentration of optimized formulation F2 was achieved in a short period of time and increased relative bioavailability and F2 was found to be stable during accelerated stability testing as per the ICH stability guidelines. Conclusion: From drug-excipient compatibility studies, disintegration time, in vitro dissolution studies, and pharmacokinetic studies, it was concluded that starch glutamate can be used as a superdisintegrant in the formulation of fast-dissolving tablets to increase the solubility as well as bioavailability of the poorly soluble drugs.